The Drosophila DmGluRA is required for social interaction and memory - Schoenfeld, Brian P. (Frontiers Media S.A., 2013)
Metabotropic glutamate receptors (mGluRs) have well-established roles in cognition and social behavior in mammals. Whether or not these roles have been conserved throughout evolution from invertebrate species is less clear. Mammals have eight mGluRs whereas Drosophila has a single DmGluRA, which has both Gi and Gq coupled signaling activity. We have utilized Drosophila to examine the role of DmGluRA in social behavior and various phases of memory. We have found that flies that are homozygous or heterozygous for loss of function mutations of DmGluRA have impaired social behavior in male Drosophila. Futhermore, flies that are heterozygous for loss of function mutations of DmGluRA have impaired learning during training, immediate-recall memory, short-term memory, and long-term memory as young adults. This work demonstrates a role for mGluR activity in both social behavior and memory in Drosophila.